REPRESENTASI IDENTITAS ETNIS PAPUA DALAM SERIAL DRAMA REMAJA DIAM-DIAM SUKA - Lintang Citra Christiani (Universitas Tidar, 2017)
This research is a cultural studies, which disscuss representation of Papuan ethnic identity in the adolescent drama series Diam-Diam Suka. The concept of postcolonial theory and John Fiske semiotic analysis “Television Codes” were used to show representation of Papuan ethnic identity that displayed by teks.The finding of this study showed that the mass media through text perpetuates the identity of Papua as a foolish, weird, and primitive one. This is done by text in several ways. First, the text emphasizes the distinction of Papuans against the majority trough appearance, cultural attributes, and the way of speech. Second, the text shows the unequal power relations between the majority-minority through setting and characterization. Third, the text attaches humor to Papuan characters through dialogue in drama series. Papuan identity is constructed under Western hegemony as well as placing Western consciousness as its center.